Students’ Satisfaction Level on Eenglish Day Program at Darul Ulum Islamic Boarding School Banda Aceh - Rahmatullah Rahmatullah; Sofyan A. Gani; Bustami Usman (English Education Journal, 2019)
The purpose of this study were to measure the level of students’ satisfaction on teachers’ supervision, assessment sessions, and the skills and learning experiences students’ got from English Day program at Darul Ulum Islamic Boarding Banda Aceh. Besides that it also want to find out whether there is a significant different between male and female students’ satisfaction toward English Day program at Darul Ulum Islamic Boarding School Banda Aceh. The data were gathered at Darul Ulum Islamic School Banda Aceh. The respondents of this study were the third year students of Darul Ulum who are enrolled in Dayah program. There were 114 students who involve as the respondents of this research. This study found that students’ at Darul Ulum Islamic School were satisfied toward English Day program at their schools (Mean = 3.71, SD = 1.06). Furthermore, there was no significant different between male and female students’ satisfaction toward the program (p-value = 0.09 0.05). However, this research found that students at Darul Ulum Islamic Boarding School felt that the grammar leaning and training in English Day program still need a lot of improvement.